Pengembangan Media Pembelajaran Berbasis Android Pada Materi Laju Reaksi - Ramlan Silaban; Pelita Ananda Sianturi (Jurnal Inovasi Pembelajaran Kimia (Journal Of Innovation in Chemistry Education), 2021)
This study aims to see whether the learning outcomes of students who are taught with Android-based chemistry learning media are higher than the KKM scores, determine the feasibility of Android-based chemistry learning media developed based on BSNP standards and determine student responses to ChamRaAte media. The media feasibility data and student responses were analyzed descriptively, while the learning outcome data were statistically analyzed with the left side t test. Based on the results of data analysis, the Android-based chemistry learning media developed met the BSNP eligibility standards with an average feasibility of 3.8 with very valid criteria and did not need to be revised. The results of student responses to ChamRaAte media obtained a total percentage of 98%, which means that students received and responded to the media very well. The results of the t test using SPSS 25 obtained sig (2-tailed)> 0.05 (0.142> 0.05) and - t table <t count (-1.729 <1.531), which means that the learning outcomes of students who are taught with Android-based chemistry learning media are higher than KKM value.